PENERIMAAN DIRI PASIEN KANKER PAYUDARA: LITERATURE REVIEW - Erika Emnina Sembiring; Adriani Natalia M (NHM PRESS, 2023)
Breast cancer is a malignancy with a high number of cases compared to other types of cancer in women. Breast cancer and its treatment therapy have psychological impacts such as stress, anxiety, low self-esteem, disturbed body image, and unpreparedness to accept the disease conditions experienced. Low self-acceptance makes breast cancer patients not enthusiastic about living life, care and treatment and have low motivation to recover. The purpose of this study was to determine the level of self-acceptance of breast cancer patients. The method used in this study is Literature Review by analyzing research articles published through PubMed, ScienceDirect. The search results obtained 37 articles and only 6 articles that met the criteria for analysis. The majority of research results show self-acceptance of breast cancer patients in the medium and low categories, and the instrument most widely used to assess self-acceptance is the Acceptance of Illness questionnaire. Self-acceptance assessment is very important to do to prevent bad psychological impact on breast cancer patients. Good self-acceptance can increase enthusiasm and motivation to recover as well as the quality of life of breast cancer patients.